If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + 7 = 3b + 2 Reorder the terms: 7 + b = 3b + 2 Reorder the terms: 7 + b = 2 + 3b Solving 7 + b = 2 + 3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3b' to each side of the equation. 7 + b + -3b = 2 + 3b + -3b Combine like terms: b + -3b = -2b 7 + -2b = 2 + 3b + -3b Combine like terms: 3b + -3b = 0 7 + -2b = 2 + 0 7 + -2b = 2 Add '-7' to each side of the equation. 7 + -7 + -2b = 2 + -7 Combine like terms: 7 + -7 = 0 0 + -2b = 2 + -7 -2b = 2 + -7 Combine like terms: 2 + -7 = -5 -2b = -5 Divide each side by '-2'. b = 2.5 Simplifying b = 2.5
| 14=x-2*3 | | -4(3x-6)+2=-12x+26 | | 0.007x+9.95=12.47 | | 2(2x-1)+(4x-3)=4(3x-5) | | 9x^3y^-10z^6/3xy^2z^-3 | | 5/8(p-4=2) | | 5x^2-20x^2y+5z-20yz= | | 35x2/7 | | (x-4)(x+8)=28 | | 13=g+9 | | -7(x-5)-9x=-45 | | 2x-2=4x+6x+8 | | 3-6x/4-8x | | 7(11-(8(c+2)-5(c+2)))=-14c | | xElN/8x10 | | 13x+6=2(6x-1)+8 | | 10=4a | | 20xyz+12x^2z-40yz= | | 3m+10=3+4m | | 2u=81-7u | | -5=-3(3x+9)+4 | | -4x^3(x^3+8x)+7x^6= | | 77=3v+17 | | 6(-1-5x)=54 | | -6(-1-5x)=54 | | T/-3-5=-2 | | 0=2n^2-7n-16 | | T/-3-5 | | 12u-9u=21 | | x*x-7x+6=0 | | (7x^5-8x)(6x^2)= | | -2+5(x-4)=12x+5-7x |